ABOUT SOME MONETARY FINDS IN FUNERARY CONTEXT FROM MOESIA INFERIOR - Gabriel M. Talmațchi (Journal of Ancient History and Archaeology)
The article analyses a number of four monetary forms of funerary accumulations that were found either accidentally or as a result of preventive archaeological excavations. These coins are dated during the early Roman period, were found near fortified centers (Carsium and Noviodunum) and vici type settlements (Poiana, not far from the capital of the province, Tomis) located in the territorial area of the province of Moesia Inferior. A total number of 19 bronze coins are listed, of which five sestertii, six dupondii and eight asses. The three small batches of coins and the hoard fall in the category of the funerary items voluntarily (intentionally) deposited in graves. All of them (but especially the first three) illustrate the often identified custom of leaving in the graves coins that were out of circulation for several decades or even longer. The coins had only a symbolic value, being mere decorative objects. The identified coins seem to generally confirm a carefully made selection of the reverse representations, according to a decision taken by the deceased’s family for his last trip. Thus, the iconographic selection illustrates the “fashionable” mentalities and superstitions specific for the corresponding chronological periods. However, sometimes, these superstitions can also be personal, which is why the analyses have to be done differently for each situation. The presence of several coins in deposits or hoards may be linked with a particular belief regarding the necessity of paying for several passes during their trip to the underworld.